The Paris diversion : a novel - Pavone, Chris (Crown, 2019)
American expat Kate Moore drops her kids at the international school, makes her rounds of chores, and meets her husband Dexter at their regular café: a leisurely start to a normal day, St-Germain-des-Prés. Across the Seine, tech CEO Hunter Forsyth stands on his balcony, wondering why his police escort just departed, and frustrated that his cell service has cut out; Hunter has important calls to make, not all of them technically legal. And on the nearby rue de Rivoli, Mahmoud Khalid climbs out of an electrician<U+2019>s van and elbows his way into the crowded courtyard of the world<U+2019>s largest museum. He sets down his metal briefcase, and removes his windbreaker. That<U+2019>s when people start to scream. Everyone has big plans for the day. Dexter is going to make a small fortune, finally digging himself out of a deep financial hole, via an extremely risky investment. Hunter is going to make a huge fortune, with a major corporate acquisition that will send his company<U+2019>s stock soaring. Kate has less ambitious plans: preparations for tonight<U+2019>s dinner party<U+2014>one of those homemaker obligations she still hasn<U+2019>t embraced, even after a half-decade of this life<U+2014>and an uneventful workday at the Paris Substation, the clandestine cadre of operatives that she<U+2019>s been running, not entirely successfully, increasingly convinced that every day could be the last of her career. But every day is also a fresh chance to prove her own relevance, never more so than during today<U+2019>s momentous events. And Mahmoud? He is planning to die today. And he won<U+2019>t be the only one.